Confined systems through variational supersymmetric quantum mechanics - Filho, E. Drigo [UNESP]; Ricotta, R. M. [UNESP] (My University, 2003)
The energy states of the confined harmonic oscillator and the Hulthén potentials are evaluated using the Variational Method associated to Supersymmetric Quantum Mechanics.
Keywords: Eigenvalues and eigenfunctions; Electron energy levels; Hamiltonians; Harmonic analysis; Mathematical operators; Oscillators (electronic); Bosonic operators; Confined systems; Harmonic oscillators; Hulthen potentials; Quantum theory